Analisis Pemilihan Supplier Bahan Baku Aluminium Menggunakan Metode AHP dan Topsis pada Ud,Morodadi Jaya Surabaya - Miftah Novi Nur Arifin; Wiwik Handayani (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Companies need to evaluate supplier performance to get those that match the company's criteria. The problem with UD. Morodadi Jaya is that there are no appropriate criteria and standards to be set in the selection of suppliers so that the company does not have supplier performance evaluations. The purpose of this study was to determine the weight of the value of each criterion used in making the decision to choose the best alternative supplier at UD. Morodadi Jaya. There are five criteria used, including: availability of goods, price, quality of goods, delivery, service. To obtain complete data, the researchers used methods in the form of interviews and filling out questionnaires. The method used in processing the data in this study is the AHP and TOPSIS methods. Based on data processing using the AHP method, the weights with the highest criteria are on the availability of goods, followed by the next rank, namely delivery, price, quality, service. Then for data processing using TOPSIS can be seen that the supplier PT. Prima Aluminum is the most potential supplier. The next alternative priority is based on the ranking in a row. Keywords: Analytical Hierarchy Process; Supplier Selection; TOPSIS